2021
DOI: 10.2109/jcersj2.20179
|View full text |Cite
|
Sign up to set email alerts
|

Improving self-healing ability and flexural strength of ytterbium silicate-based nanocomposites with silicon carbide nanoparticulates and whiskers

Abstract: In the emerging era of aircraft industry, silicon carbide (SiC) is regarded as an appropriate material for gas turbine engine blades. In order to protect this ceramic component against the oxidation and volatilization in hot steam environments, environmental barrier coating should be utilized. The composite of SiC/Yb 2 Si 2 O 7 Yb 2 SiO 5 with self-healing ability is a candidate for the top layer of this coating. In this study, the crack-healing behavior of SiC/Yb 2 Si 2 O 7 Yb 2 SiO 5 nanocomposites is invest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Regarding crack healing and new crack initiation, smaller SiC particles may have caused more rapid volume expansion owing to their larger specific areas. In a previous study, 21) it was reported that a Yb 2 Si 2 O 7 / SiC sintered body using two types of SiC shapes, SiC particles with a specific surface area of 17.16 m 2 /g and SiC whiskers with a specific surface area of 8.47 m 2 /g, showed better self-healing properties when SiC particles with a larger specific surface area were used. The current results of our study are considered valid, as similar results have been also reported 19) for the thermal spray coatings at an oxidation time of 100 h. Next, we focused on SiC content.…”
Section: Self-healing Propertymentioning
confidence: 98%
“…Regarding crack healing and new crack initiation, smaller SiC particles may have caused more rapid volume expansion owing to their larger specific areas. In a previous study, 21) it was reported that a Yb 2 Si 2 O 7 / SiC sintered body using two types of SiC shapes, SiC particles with a specific surface area of 17.16 m 2 /g and SiC whiskers with a specific surface area of 8.47 m 2 /g, showed better self-healing properties when SiC particles with a larger specific surface area were used. The current results of our study are considered valid, as similar results have been also reported 19) for the thermal spray coatings at an oxidation time of 100 h. Next, we focused on SiC content.…”
Section: Self-healing Propertymentioning
confidence: 98%
“…Consequently, self-healing nanocomposites have been used to produce fixed and mobile jet engine components [118,119]. In particular, for aerospace combustion chambers, selfhealing nanocomposites have been designed [120,121]. In addition to high temperature, pressure, and damage resistance, self-healing nanomaterials revealed corrosion resistance properties for engine components [122].…”
Section: Aerospace Enginesmentioning
confidence: 99%
“…chambers, self-healing nanocomposites have been designed [120,121]. In addition to high temperature, pressure, and damage resistance, self-healing nanomaterials revealed corrosion resistance properties for engine components [122].…”
Section: Aerospace Enginesmentioning
confidence: 99%
“…Recently, materials that utilize chemical reactions as a healing (repair) function have been developed and studied. Conventional self-healing ceramics utilize oxidation reactions of non-oxides as the healing function and can only be used at temperatures above 800 • C [1][2][3][4][5][6]. To further expand the range of applications, lowering the temperature at which healing occurs is investigated.…”
Section: Introductionmentioning
confidence: 99%